Dimensions of organizational justice impact job satisfaction and turnover intention emerging economics - Galván Vela, Esthela; Ravina-Ripoll, Rafael; Ahumada-Tello, Eduardo; Tobar-Pesántez, Luis Bayardo (My University, 2022)
When the individual exercises a function in society, due to his or her efforts at work, he or she manifests multiple emotions that translate into behaviour. In recent years, the study of organisational behaviour has been a topic of interest in the economic and administrative sciences. Due to the importance of studying the elements that makeup employee behaviour, the objective was to analyse the influence of the dimensions that make up perceived justice, such as distributive justice, procedural justice and interactional justice, on job satisfaction and turnover intention. The data obtained from five hundred fifty-five workers in Mexico's food industry were analysed using the structural equation technique by CB-SEM. The results suggest a correlation between all the variables in the study. In this respect, it should be noted that there are positive relationships among distributive, interactional, job satisfaction and distributive justices on turnover intention. The results suggest the importance of considering business practices that enrich the feelings of justice among employees to avoid developing negative feelings towards the company that may result in job abandonment. RESUMEN Cuando el individuo ejerce una función en la sociedad, debido a su esfuerzo en el trabajo, manifiesta múltiples emociones que se traducen en comportamiento. En los últimos años, el estudio del comportamiento organizacional ha sido un tema de interés en las ciencias económicas y administrativas. Debido a la importancia de estudiar los elementos que componen el comportamiento de los empleados, el objetivo fue analizar la influencia de las dimensiones que componen la justicia percibida, como la justicia distributiva, la justicia procedimental y la justicia interaccional, sobre la satisfacción laboral y la intención de rotación. Los datos obtenidos de quinientos cincuenta y cinco trabajadores de la industria alimentaria de México se analizaron mediante la técnica de ecuaciones estructurales por CB-SEM. Los resultados sugieren una correlación entre todas las variables en estudio. En este sentido, cabe señalar que existen relaciones positivas entre las justicias distributiva, interaccional, de satisfacción laboral y distributiva sobre la intención de rotación. Los resultados sugieren la importancia de considerar prácticas empresariales que enriquezcan los sentimientos de justicia entre los empleados para evitar desarrollar sentimientos negativos hacia la empresa que puedan derivar en el abandono del trabajo.
Polish journal of management studies
Keywords: Organisational justice; Job satisfaction; Turnover intention; Campus Tijuana